2016
DOI: 10.1371/journal.pone.0164090
|View full text |Cite
|
Sign up to set email alerts
|

Blood Component Therapy and Coagulopathy in Trauma: A Systematic Review of the Literature from the Trauma Update Group

Abstract: BackgroundTraumatic coagulopathy is thought to increase mortality and its treatment to reduce preventable deaths. However, there is still uncertainty in this field, and available literature results may have been overestimated.MethodsWe searched the MEDLINE database using the PubMed platform. We formulated four queries investigating the prognostic weight of traumatic coagulopathy defined according to conventional laboratory testing, and the effectiveness in reducing mortality of three different treatments aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…It should be noted that although no specific guidelines for management of post‐PDT bleeding are available, the last version of the European Society of Anaesthesiology (ESA) guidelines for management of perioperative bleeding suggested that the use of rFVIIa could be considered for “bleeding which cannot be stopped by conventional, surgical or interventional radiological means and/or when comprehensive coagulation therapy fails” . In our case, correction of confounding factors (ie, acid‐base unbalance, hypocalcemia, hypothermia), administration of tranexamic acid, and correction of hypofibrinogenemia were performed according to guidelines, in association with a first platelet unit transfusion . However, these measures did not stop bleeding leading us to consider the use of rFVIIa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that although no specific guidelines for management of post‐PDT bleeding are available, the last version of the European Society of Anaesthesiology (ESA) guidelines for management of perioperative bleeding suggested that the use of rFVIIa could be considered for “bleeding which cannot be stopped by conventional, surgical or interventional radiological means and/or when comprehensive coagulation therapy fails” . In our case, correction of confounding factors (ie, acid‐base unbalance, hypocalcemia, hypothermia), administration of tranexamic acid, and correction of hypofibrinogenemia were performed according to guidelines, in association with a first platelet unit transfusion . However, these measures did not stop bleeding leading us to consider the use of rFVIIa.…”
Section: Discussionmentioning
confidence: 99%
“…13 In our case, correction of confounding factors (ie, acid-base unbalance, hypocalcemia, hypothermia), administration of tranexamic acid, and correction of hypofibrinogenemia were performed according to guidelines, in association with a first platelet unit transfusion. 13,14 However, these measures did not stop bleeding leading us to consider the use of rFVIIa. Since the administration of rFVIIa does not resolve the cause of bleeding per se, it should be considered as a "not specific" form of coagulation support.…”
Section: Discussionmentioning
confidence: 99%